Game, Set, and Match: Do Women and Men Perform Differently in Competitive Situations? - Michael Jetter; Jay K. Walker (Institute for the Study of Labor (IZA), 2015)
This paper analyzes potential gender differences in competitive environments using a sample of over 100,000 professional tennis matches. We focus on two phenomena of the labor and sports economics literature: the hot-hand and clutch-player effects. First, we find strong evidence for the hot-hand (cold-hand) effect. Every additional win in the most recent ten Tour matches raises the likelihood of prevailing in the current encounter by 3.1 (males) to 3.3 percentage points (females). Second, top male and female players are excelling in Grand Slam tournaments, arguably the most important events in tennis. For men, we also find evidence for top players winning more tie-breaks at Grand Slams. Overall, we find virtually no gender differences for the hot-hand effect and only minor distinctions for the clutch-player effect.
Keywords: J24; L83; D84; 330; gender gap; competition; hot hand; clutch player; tennis